Analisis Tingkat Kepercayaan Masyarakat terhadap Kinerja Polri Tahun 2023: Analisis Tingkat Kepercayaan Masyarakat terhadap Kinerja Polri Tahun 2023 - Saputra, Azis; Sutrasno, Dadang; Setiawan, Widi (Jurnal Litbang Polri, 2024)
Research of public trust in the performance of the National Police aims to measure the level of public trust in the performance of operational functions, namely Binmas, Intelkam, Lalu lintas, Criminal Investigation and Sabhara. This research uses quantitative and qualitative methods. The quantitative method used survey and the qualitative method used Focus Group Discussion. The results show Public Trust Index is 85.77 in the Very Good category. Binmas: 84.16; Intelkam: 87.10; Lantas: 83.83; Reskrim: 86.67; and Sabhara: 87.08. The regression results of the questionnaire data that influence each function are categorized as; a) superior, b) improvement, c) improvement. Diversity public perceptions and expectations shows that public is very enthusiastic about the service programs provided, such as: Bhabinkamtibmas approach, improving technological facilities and infrastructure, increasing cybercrime investigation capabilities, and patrolling vulnerable areas. Meanwhile, the police's internal perspective has also made breakthroughs and service innovations, such as: optimizing the Police presence in living environment, applying technology in operational services, and forming special teams for crime control. However, there are still obstacles for Polri in providing excellent service to community, limited technological facilities and infrastructure in the region, the lack of a culture of orderly community traffic, and the limited quality of human resources for investigators. Therefore, the recommendations given are adjusted from the results of regression tests in each function, namely 1)taking steps to maintain superior category services, 2)taking steps to improve category services that need to be improved, and 3)taking steps to steps to revitalize services that need improvement.